2018
DOI: 10.1038/s41598-017-18978-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids sex-specifically modulate guinea pig postnatal development via cortisol concentrations

Abstract: Early ontogenetic periods and postnatal maturation in organisms are sex-specifically sensitive to hypothalamic-pituitary-adrenal (HPA)-axis activities, related glucocorticoid secretions, and their effects on energy balance and homeostasis. Dietary polyunsaturated (PUFAs) and saturated (SFAs) fatty acids potentially play a major role in this context because PUFAs positively affect HPA-axis functions and a shift towards SFAs may impair body homeostasis. Here we show that dietary PUFAs positively affect postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Indeed, they can diminish glucocorticoid secretion through the modulation of the hypothalamicpituitary-adrenal (HPA) axis, thus resulting in a positive influence on structural growth rates. 67,68 On the contrary, an excess of dietary n-6 PUFA has shown a stimulation of adipogenesis and the development of adipose tissue in mice. 69 In our previous study, 23 Italian Duroc piglets had a higher body weight compared to Italian Landrace and Italian Large White piglets at day 3 after birth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Indeed, they can diminish glucocorticoid secretion through the modulation of the hypothalamicpituitary-adrenal (HPA) axis, thus resulting in a positive influence on structural growth rates. 67,68 On the contrary, an excess of dietary n-6 PUFA has shown a stimulation of adipogenesis and the development of adipose tissue in mice. 69 In our previous study, 23 Italian Duroc piglets had a higher body weight compared to Italian Landrace and Italian Large White piglets at day 3 after birth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Increasing PGF2 is usually regarded as an important phase in the labor procedure (17). Previous research has revealed that dietary polyunsaturated fatty acids (PUFAs) may also affect steroid hormone levels (18,19).…”
Section: Discussionmentioning
confidence: 99%